Deferred treatment is a safe and viable option for selected patients with mantle cell lymphoma. Issue 12 (2nd December 2018) - Calzada, Oscar; Switchenko, Jeffrey M.; Maly, Joseph J.; Blum, Kristie A.; Grover, Natalie; Mathews, Stephanie; Park, Steven I.; Gordon, Max; Danilov, Alexey; Epperla, Narendranath; Fenske, Timothy S.; Hamadani, Mehdi; et al.
Abstract: Prospective identification of candidates for deferred therapy is not standardized and many patients receive immediate therapy regardless of risk. We conducted a retrospective, multi-center cohort analysis of MCL patients with comprehensive clinical data to examine the use and safety of deferred therapy for newly diagnosed patients. Previously untreated patients ≥18 years-old with MCL diagnosed in 1993–2015 at five academic sites were included. Of 395 patients, 72 (18%) received deferred therapy (defined as receipt of first treatment >90 days following initial diagnosis). Patients receiving deferred therapy were more likely to have an ECOG performance status of 0 (67 versus 44% p  = .001), have no B symptoms (83 versus 65% p  = .003) and have normal LDH levels at diagnosis (87 versus 55% p  < .001). In multivariable analysis, deferred therapy was not associated with a significant difference in OS (HR 0.64: 95% CI 0.22–1.84, p  = .407).